IMPLEMENTATION OF GOOD AGRICULTURAL PRACTICES (GAP) IN IMPROVING THE QUALITY AND SAFETY OF AGRIBUSINESS PRODUCTS - Sulfiana Sulfiana (CV. Adiba Aisha Amira, 2025)
Implementation of good agriculture or Good Agriculture Practices (GAP) from the producer's perspective is a concept that guarantees the welfare of farmers, their families and workers, while from the consumer's perspective they get products of high quality and safe nutritional value. The GAP concept also guarantees environmental sustainability, so that the implementation of GAP can restore the condition of agricultural land which is increasingly damaged due to the use of chemical inputs. Demands for environmental sustainability will become increasingly stringent, even though at the same time population pressure on land resources will also become stronger. Facing these challenges and consumer demands, and in order for agricultural products to be more globally competitive, agricultural practices need to be perfected, so that they are more productive and efficient and more responsible to consumers, farm workers and the environment. These agricultural practices are Good Agricultural Practices (GAP). GAP covers the product certification process from before the seeds are planted until they leave the farm. Implementation of Good Agriculture Practices (GAP) is a holistic approach with an emphasis on activities that can affect production quality, the environment and occupational health and safety. Sustainable management of GAP is not just for market interests but has become a national commitment that long-term sustainable development is determined by a balance of attention between humans and the environment, in other words the agricultural sector is expected to be able to produce products with positive benefits in the environmental, social and economic fields.